Dimensi - Dimensi Strategis Administrasi Publik dalam Islam (POLITEA, 2018)
Strategic Dimensions of Public Administration in Islam. Public administration as the work of government to governance all resources in serving public to gain public welfare. Therefore there are some strategic dimensions concerning to the governance of public administration such as public policy, structure of  organization, management, ethic, environment and performance. Those dimensions would not running and inter connected well, when the values are different and bad behaviour such as corruption, laziness, ego, still become apart of public administrators. The value of Islam as the believe to Allah, guide the human to life and work well, dependently or independently. Islam govern the society to runs Allah’s rules in their daily life. This paper through literature research tried to explaining how the values of Islam covering the strategic dimensions in public administration. As a moslem country, Indonesia needs to understand how’s the values of Islam and how to implement the values in their daily lives.           Keywords: the values of islam, public administration, the work of government.